Taguchi based grey relational analysis for multi-performance optimization of slab milling process parameters - Arshad, Noor Siddiquee; S. F. Khan; Ghulam, Abdul Quadir; Zahid A. Khan; Pankul, Goel; Shahrul, Kamaruddin (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.